The Formation of Covid-19 Term Based on Morphology and Terminology in al Arabiya Daily News - Lubna Lubaba; Darsita Suparno; Waki Ats Tsaqofi (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2022)
The impacts caused by the Covid-19 pandemic include the language system and the emergence of newly known and used terms. Based on that, this research aims to determine the origin of the formation of the term. The method used in this research is descriptive qualitative method and verification, explaining and testing the concept of the term Covid-19. While the theory used is morphology, terminology, and translation. The study results came from six Al Arabiya online daily news articles with the discovery of the term Covid-19 as many as six with a classification of three words and three phrases. The daily news was accessed- from March 2020 to May 2021 at different times. The term Covid-19 in Indonesian and Arabic comes from the direct translation process of the English term. The study results also explain that the Indonesian people actively use the term Covid-19 in English because the Indonesian language equivalent is slow, and people are used to communicating with the English term.